The Effectiveness of Problem Based Learning (PBL) Method in Teaching Reading - Ahmad Zuhri Rosyidi (Universitas Muhammadiyah Mataram, 2018)
This pre-experimental research aimed to find out the effectiveness of problem based learning in teaching narrative type of reading text at the tenth grade of public senior high school (SMAN) 1 Sukamulia, East Lombok. The sample of this research consisted of 30 students taken through purposive sampling. A pre-test and a post-test were used to collect the data on the reading ability of the students, and observation list was employed to gather the data on how problem based learning involves the students in the learning process. The collected data were then analyzed using descriptive statistic and paired-sample t-test to answer the hypothesis. The result of data analysis revealed that there was a significant difference between the pre-test and the post-test scores, t(df=29) = 5.203 at p = 0.000, meaning that the null hypothesis is rejected (Ho) and alternative hypothesis is accepted (Ha).It means that there was a significant effect of problem based learning method in teaching critical reading for the tenth graders of SMAN 1 Sukamulia.